2017
DOI: 10.5742/mewfm.2017.93133
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Suicide Attempt in Tabriz, Iran

Abstract: Objective: Suicide is among the main problems in society and is caused by many factors. These factors are different between developed and developing countries. This research was performed to investigate the epidemiological data related to patients who attempted suicide by poisoning in Tabriz, north west Iran. Materials and Methods: Throughout a four-month period, 300 self-poisoned patients (168 females and 132 males) referring to Sina educational hospital in Tabriz , were evaluated by a general psychiatrist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The present study, as well as other studies (18,(31)(32)(33)(34) suggest that marital conflicts and family disputes are the most important risk factors for SAs in Iranian communities; particularly, among couples who suffer from early marriages with the lack of skills for life management and poor levels of education. Some systematic reviews (32,33) and a case-control study (34) in Iran have revealed that the family and marital conflicts are the most important factors for SA.…”
Section: Discussionsupporting
confidence: 70%
“…The present study, as well as other studies (18,(31)(32)(33)(34) suggest that marital conflicts and family disputes are the most important risk factors for SAs in Iranian communities; particularly, among couples who suffer from early marriages with the lack of skills for life management and poor levels of education. Some systematic reviews (32,33) and a case-control study (34) in Iran have revealed that the family and marital conflicts are the most important factors for SA.…”
Section: Discussionsupporting
confidence: 70%